Optimal Control Method for Solving the Cauchy-Neumann Problem for the Poisson Equation - Guliyev, H.F.; Gasimov, Y.S.; Zeynalli, S.M. (Журнал математической физики, анализа, геометрии, 2014)
In the paper, the ill-posed Cauchy-Neumann problem is considered for the Poisson equation. The problem is reduced to the optimal control problem that is regularized. Optimization methods are applied to the solution of the obtained problem. Рассмотрена некорректная задача Коши-Неймана для уравнения Пуассона. Задача сведена до задачи оптимального управления. Для решения полученной задачи использованы методы оптимизации.